2022
DOI: 10.1002/hsr2.559
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anxiety, depression, and stress among students of Jahangirnagar University in Bangladesh

Abstract: Background and Aims Anxiety and depression, as well as stress, are well‐known problems observed across the world, particularly among students. This study intends to identify the level of anxiety, depression, and stress among university students and determine its association with their sociodemographic characteristics. Methods The primary data were collected from 351 students with the help of a self‐administrated questionnaire consisting of sociodemographic information and contains the Depression, Anxiety and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1
5

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 46 publications
2
10
1
5
Order By: Relevance
“…This figure falls within the prevalence rates reported across different studies in a similar population. Accordingly, compared to the finding of the current study, a higher prevalence rate of depression, anxiety, and stress was found among students from Uganda (Maria Najjuka et al, 2020), Bangladesh (Hossain et al, 2022), and Malaysia (Fauzi et al, 2021).…”
Section: Discussioncontrasting
confidence: 92%
“…This figure falls within the prevalence rates reported across different studies in a similar population. Accordingly, compared to the finding of the current study, a higher prevalence rate of depression, anxiety, and stress was found among students from Uganda (Maria Najjuka et al, 2020), Bangladesh (Hossain et al, 2022), and Malaysia (Fauzi et al, 2021).…”
Section: Discussioncontrasting
confidence: 92%
“…This study revealed the lower sleep quality of the foundation students would lead to a higher chance of depressive symptoms among foundation students, and the higher academic stress perceived by the student will increase the events of the students to experienced depressive symptoms. The past literature supports the finding of this study, students who have sleeping issues and due to a variety of academic challenges in the university have become the significant causes of depression among the students in university (Hossain et al, 2022).…”
Section: Discussionsupporting
confidence: 87%
“…Weaving is one of the world's oldest surviving crafts (27). It is an important cottage industry in developed and developing countries, including India, Pakistan, Bangladesh, Iran, Turkey, and China, where traditional weaving methods remain widely prevalent (28). Every year, over 1.5 million weavers, dyers, hand spinners, embroiderers, and other employees utilize over 0.3 million operating looms to produce 620 million metric tons of cloth (29).…”
Section: Resultmentioning
confidence: 99%